Gun regulation in Malaysia : enforcement or prevention / Faten Fathonah Kamarudin … [et al.] - Kamarudin, Faten Fathonah; Ghazali, Norliana Akmar; Yussoff, Nur Shahida Azira; Omar, Siti Sha Erdawati; Abdul Rahman, Muhammad Elmy Afyfy (Faculty of Law, 2014)
This research discusses on the enforcement of gun control regulation in Malaysia, the focal point of this research is the prevention strategy is more important rather than enforcement of gun control regulation. By definition, enforcement means the act of compelling observance of or compliance with a law while prevention means the action of stopping something from happening. Malaysia gun control regulation is too focused on enforcement, such as the prosecution approach, the process of purchasing firearms and the licensing system. However, there is insufficient focus on prevention, such as acknowledgement from a family member as a crucial element to obtain license. An approach that was taken to make this research adequate is qualitative method. Four research questions are posed, in order to make the discussion well-structured and organized. Primary and secondary data are collected from many sources in order to provide a well comprehensive research. Field work such as interview was also conducted for confirmation and verification of the informal information that had been gathered. As a conclusion, this research was made with hope that it could be made as a reference in the near future on any improvement of gun control regulation in Malaysia and it is adequate to meet the need of the reader.